2016
DOI: 10.17269/cjph.107.5209
|View full text |Cite
|
Sign up to set email alerts
|

Canadian brain cancer survival rates by tumour type and region: 1992–2008

Abstract: OBJECTIVES: To investigate patterns of survival among brain cancer patients in Canada.METHODS: Canadian Cancer Registry data were obtained for all patients with first-ever primary malignant brain tumours diagnosed between 1992 and 2008 (n = 38,095). Follow-up ended with patient death or December 31, 2008, whichever occurred first. Crude Kaplan-Meier estimates were calculated at one, two and five years post-diagnosis. Cox proportional hazard models were used to obtain adjusted hazard ratios by region for major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Glioma of adult onset are heterogeneous in their subtypes and behaviour; however, the overall prognosis of these tumours even after induction of early remission is poor . This is exemplified by our data, which show 41.4% of individuals in this study to have deceased at a mean follow‐up of 8.2 years.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Glioma of adult onset are heterogeneous in their subtypes and behaviour; however, the overall prognosis of these tumours even after induction of early remission is poor . This is exemplified by our data, which show 41.4% of individuals in this study to have deceased at a mean follow‐up of 8.2 years.…”
Section: Discussionmentioning
confidence: 56%
“…The effects of cranial radiotherapy (cXRT) on pituitary function have been well studied in cancer survivors of childhood onset; however, the consequences of cXRT on pituitary function have been less well characterized in individuals with adult‐onset brain tumours . Adult‐onset and childhood‐onset brain tumours behave differently, with adult‐onset tumours being more aggressive and associated with a significantly higher rate of relapse and mortality . Similarly, endocrinologically, there appears to be a dichotomy in the radio‐sensitivity of the hypothalamic‐pituitary (HP) axis of adults and children, with children showing greater susceptibility to radiation‐induced hypopituitarism.…”
Section: Introductionmentioning
confidence: 99%
“…There were 135 potentially eligible studies, of which 63 were included in this review after full eligibility assessment (Fig. 1 ) 9 37 . One study reported two distinct populations 14 .…”
Section: Resultsmentioning
confidence: 99%
“…More than 1.7 million new cancer cases and over 600,000 cancer deaths are estimated in 2019 in the United States alone (Siegel et al, 2019). Brain cancer is one of the deadliest cancer types with low survival rates among both women and men (Siegel et al, 2016;Yuan et al, 2016). Cancer research relies on accurate and reproducible disease characterizations in order to better understand what triggers cancer and how cancer progresses so that more effective means of evaluating cancer interventions can be developed.…”
Section: Introductionmentioning
confidence: 99%